The Extreme searcher's internet handbook : - Hock, Randolph (CyberAge Books, 2013)
This fully revised handbook details what users must know to take full advantage of internet search tools and resources. From the latest online tools to the new and enhanced services offered by standbys Google and Yahoo!, this revamped edition also features chapters on popular social networking sites such as Twitter, YouTube, Facebook, and LinkedIn as well as a collection of up-to-date screenshots for visual reference